Os sertões no século XXI: a beleza que Euclides não viu - Cabello, Camila Faustinoni (2016)
The result of an interdisciplinary formative experience and an empirical, theoretical and documentary research, this work consists in the union of a cultural network , composing an audiovisual ethnography of Canudos in the its backlands, from the point of view of women during the twenty-first century. The historical invisibility to which women were subjected confirmed again when Euclides da Cunha in the book Rebellion in the Backlands, reduces the narrative and the registers of their stocks to almost null, even though they were the majority of the population in Antonio Conselheiro group. The past acts inevitably on this, especially when living in a soil that absorbed the blood of thousands of victims of genocide filed in the name of the order, hidden under the cloak of the democracy and silenced by the ideological apparatuses of the state for a long time. Canudos went through the extermination in a bloody war promoted by the State (1896-1897); It reorganized in 1910 on the ruins of Belo Monte, which was totally flooded by the construction of Cocorobó’s Dyke in 1969. Canudos waz reconfigured around the dam, constituting a municipality in 1985. The force of history, culture and society acts on the people who develop their range of meanings, from perspectives about themselves, others and about the world, powered by their own personal imagination and life story. The union between biographies and cultures is the main object of this research, which plunges into the imagination and reality of women who now live in Canudos. Ethnography and ethnobiography are methodological principles that guides this research, which we conceptually foresee an experimental and transmedia material, that combines different views such as photography, audiovisual, textuality and orality in order to cover the complexity of the cultural dimension of the characters as well as the expression and dissemination of the narratives constructed by the author, arranged in a postmodern cultural network, to be consolidated in a web documentary.